2009
DOI: 10.1111/j.1651-2227.2008.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference in relation to body perception reported by Finnish adolescent girls and their mothers

Abstract: WC rather than BMI agrees with perception of body size, possibly due to its relation to abdominal fat at different ages. For effective prevention and treatment programmes for weight-related health problems among adolescent girls, we recommend measuring WC to diminish the discrepancy between measured and perceived body size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…WC rather than BMI agrees with perception of body size, possibly due to its relation with abdominal fat at different ages [40], and could serve better than BMI and skin fold thickness for identifying central adiposity [41]. WC has been shown to have a significant role in identifying overweight and obese individuals [42].…”
Section: Discussionmentioning
confidence: 99%
“…WC rather than BMI agrees with perception of body size, possibly due to its relation with abdominal fat at different ages [40], and could serve better than BMI and skin fold thickness for identifying central adiposity [41]. WC has been shown to have a significant role in identifying overweight and obese individuals [42].…”
Section: Discussionmentioning
confidence: 99%
“…21 With regard to the association between body overestimation and WC in girls, these results differ from those of two other studies conducted with female schoolchildren. In a study conducted in Finland by Van Vliet et al, 38 WC was associated with more accurate body estimation, whereas in a study conducted in Australia by Frederickson et al, 22 WC was associated with greater underestimation of body size. Some of these differences can be attributed to the different cutoff…”
Section: Statistical Analysesmentioning
confidence: 91%
“…It is therefore not surprising that the majority of disturbances in body perception start during adolescence, a period of rapid physiological changes [33]. In our previous work, waist circumference (WC) was found to correlate more closely with body perception than BMI in adolescent girls [7], implicating that body fat distribution mediates body size estimation. Rhodes et al [34] showed that obese women with prominent body fat distribution concentrated in visible areas such as the face, chest, and waist, overestimate their doi: 10.7243/2052-935X-2-1 body size and feel heavier than they actual are.…”
Section: Discussionmentioning
confidence: 99%
“…Waist circumference (WC) has been shown to correlate more closely with body perception than BMI in European adolescent girls [7]. As WC is an important measure of body fat distribution and fat accumulation in the abdominal region [8], this implicates that body perception is related to body fat distribution.…”
Section: Introductionmentioning
confidence: 99%